Tafsir Al-Qur’an Relevansinya Terhadap Pendidikan - Nurul Hidayah Siregar; Zulheldi Zulheldi; Duski Samad (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This article aims to analyze the interpretation of the Qur'an in its relevance to education. This research uses library research method, with documentation data collection technique. The primary source used in this article is the Qur'an while the secondary sources used in this article are books related to the interpretation of the Qur'an. The results showed that tafsir al-qur'an is a science for a series of explanations about the verse of the Qur'an done by a mufasir to find out the meaning contained in the verse of Al-Qu'an. Its relevance to the education verse is the number of verses of the Qur'an that discuss education, namely there is also a relevance to education in QS. al-alaq: 1-5, QS.Al-hajj: 41 and QS. Al-Maidah: 67.